การวิเคราะห์ความได้เปรียบโดยเปรียบเทียบการส่งออกสินค้าของไทยไปในกลุ่มอาเซียนบวกสาม - เสาวภาคย์ โล่ห์เพ็ชร (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This study aimed at analyzing the impact of opening ASEAN+3 free trade and the advantages of important agricultural product of Thailand comparing to other countries in ASEAN+3 . The revealed comparative advantage (RCA) and Global trade analysis Project (GTAP Model) were used for analysis. It addition, The general condition of each country in ASEAN+3 was studied. Moreover, important agriculture product were select from ต most imported and exported products in 2011. They were divided according to the customs tariff in harmonized system 2007, 2 digits by making use of data from 2007-20011. From the study on export of important Thai's agriculture products to ASEAN+3 economy, it was found that agriculture products of Thailand had advantages compared with the competitions with every product in the list from 2007-2011. The products with the most advantage were sugar products and sugar confectionery, then, rubber product and other articles of rubber. In term of the impact from opening ASEAN+3 economy. it was revealed that gross domestic products of china, Japan, South Korea as well as, Thailand generally decreased. In terms of changes in the trade balance, all ASEAN member countries tend to had increased trade balanced, except Thailand and countries in ASEAN+3. In terms of import and export values, all countries in ASEAN member Countries and ASEAN+3 includes Thailand generally decreased. For the price index of